Urban Landscape Change Effects on Flood Resilience in the Ecological Structure of University Belt, Manila, Philippines - Sibayan Flora Mae; Navarra Nappy L.; Santos Selena Balbino (BIO Web of Conferences)
Through biotope mapping and assessment, this study evaluated the ecological structure of the University Belt watershed in highly urbanized Manila, vulnerable to flooding due to proximity to the Pasig River and Manila Bay. An Ecological Plan was proposed to enhance the ecological value and flood resilience of Existing Ecological Structures in the site. Seven (7) biotopes were identified. Coastal Green Space and Lowland Green Space, located near the coast, comprised 8.95% of total land area (2450 ha). Urban, Industrial, Residential, Institutional, and Informal Settlements, dominant built-up areas, comprised 91.05% of total land area. Coastal Green Space garnered D2, A6, R4, and H3 biotope assessment ratings, while Lowland Green Space scored D1, A7, R4, and H2, underscoring their high ecological value. Intramuros Green Space, Rizal Park, and Malacañang Green Space were identified as three (3) Ecological Cores having high ecological value. Several strategies were proposed to improve the site’s ecological value and flood resilience. Preservation and expansion of the Ecological Cores were recommended to mitigate stormwater runoff. Interventions such as vegetated river embankments were suggested for Corridors to limit encroachment of impervious surfaces near waterways. Along the Ecological Edge, protecting green spaces was advised to mitigate coastal development impacts